EDGE DETECTION IN IMAGES - Pekšs, Uģis; Pobjaržans, Deniss; Peiners, Romāns; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Proposed research is completed to find edges in plywood boards.The goal of work is to compare different technologies and methods and find best suitedt technology to find edges. Reseach study concluded that there are many abstain what have to be taken first to find edges, like light and angle. And best suited technology to find edges is MATLAB and best mothod is depending on abstain in what picture was taken in.